ADCY6 is a potential prognostic biomarker and suppresses OTSCC progression via Hippo signaling pathway - Sen Yang; Li‐Juan Guo; Yong Liang; Zhi‐Ming He; Jia Luo; Yan‐Dong Mu (Kaohsiung Journal of Medical Sciences, 2023)
Abstract Oral tongue squamous cell carcinoma (OTSCC) is a malignant tumor. Recently, studies have found that adenylate cyclase 6 (ADCY6) plays a pivotal role in many lethal tumors formation processes. The role of ADCY6 in OTSCC remains unknown. The expression of ADCY6 in OTSCC tissue samples was detected. The clinical significance of ADCY6 in OTSCC was analyzed by statistical methods. OTSCC cell lines were selected to analyze the biological function of ADCY6. Meanwhile, the effect of ADCY6 on the growth of OTSCC in vivo was explored using subcutaneous tumorigenesis assay. WB assay was used to detect the underlying signaling pathway. Cell function recovery test used to investigate the mechanism of ADCY6‐promoting OTSCC malignant biological behavior via Hippo signaling pathway. We report that ADCY6 was obviously downregulated in OTSCC tissue samples and cell lines. Importantly, lower expression of ADCY6 indicates a poorer prognosis in patients with OTSCC, and its expression is significantly correlated with TNM stage and tumor size. Functionally, forced expression of ADCY6 can significantly inhibit the proliferation, migration, invasion, and promote apoptosis of OTSCC cells. Mechanistically, we demonstrated that ADCY6 upregulation impaired Hippo signaling pathway to reduce the malignant biological behavior of OTSCC. Generally, our findings suggest that ADCY6 suppressed Hippo signaling pathway to regulate malignant biological behavior in OTSCC, which provide new cues for further exploring the mechanism of occurrence and development of OTSCC.